(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Wind energy, generated by wind power, refers to producing electricity through wind or air flows that occur naturally in the earth’s atmosphere. Modern wind turbines capture kinetic energy from the wind and convert it into electricity. A windmill converts wind energy into electrical or mechanical energy that can be used to pump water or grind cereals. The most common windmills in use today are three-bladed, horizontal-axis windmills with the nacelle mounted on steel towers that can be cylindrical steel plate towers or lattice towers. Since 1977, this modern windmill concept has become the industry standard. The research design used in this study was quantitative experimental research while utilizing purposive sampling. The statistical treatment used in this study was a T-test to determine the difference between two groups of respondents. Using the questionnaire as the research instrument, the researchers surveyed to identify the level of acceptability of the model in terms of construction materials, design, mechanism, and presentation. The study’s respondents consisted of 4 Mechanical Engineers and 4 Electrical Engineers. The following procedures were undertaken in the process of developing the model: Collect the materials that will be used in the wind turbine, build a basic structure of the wind turbine and the house, put a DC motor in the structure, and use the glue stick to seal, attach the wire in the DC motor and LED bulb. The study results regarding Construction Materials, Design, Mechanism, and Presentation are Acceptable. The overall weighted mean of Mechanical Engineers is 3.54 is Highly Acceptable, and the overall weighted mean of Electrical Engineers is 3.06 as Acceptable. The t-score is 4.952, and the t-critical is 2.447. It indicates a significant difference between the two groups of respondents. For further project improvement, the respondents recommended using strong materials for the frame and support of the prototype and hard but lightweight materials for the wind turbine blades. The researchers should improve the model and do in-depth research for the improvement of the model.